Analysis of Autophagy Induction through ATG16L1 Phosphorylation - Tian, Wensheng (Université d'Ottawa / University of Ottawa, 2020)
Autophagy is a degradative program that maintains cellular homeostasis and is responsible for clearing potentially toxic elements from the cell. Defects in autophagy have been described in pathophysiology including neurodegeneration, cancer, and inflammatory bowel disease. However, analysis of autophagy rates can be challenging, particularly in rare cell populations or in vivo, due to inherent limitations of current tools available for measuring autophagy pathway induction. Here, we describe a novel method to monitor autophagy by measuring post-translational modification of the protein ATG16L1. We developed and characterized a monoclonal antibody that can detect phospho-ATG16L1 endogenously in mammalian cells by western blot, immunofluorescence, and immunohistochemistry. We demonstrate that phosphorylation of ATG16L1 provides a readout for the level of active E3-like enzyme responsible for lipidating LC3B, which can be used to determine autophagy rates. Importantly, phospho-ATG16L1 is only present on newly-forming autophagosomes. Therefore, its levels are not affected by prolonged stress or late-stage autophagy blocks, which can confound autophagy analysis. Moreover, we show ATG16L1 phosphorylation by the autophagy kinase ULK1 is a conserved signaling pathway that is activated by numerous autophagy-inducing stressors. Taken together, analysis of ATG16L1 phosphorylation represents an exciting new tool for researchers to study autophagy induction.
Keywords: Autophagy; ATG16L1; Phosphorylation; ULK